Treatable myopathies - Goh, Khean Jin (University of Malaya, 2021)
Neuromuscular disorders are a relatively uncommon and heterogeneous group of disorders involving the peripheral nervous system and consist of diseases of the anterior horn cell, peripheral nerve, neuromuscular junction and muscle. Of these, diseases of the muscle, myopathies are probably the least common compared the other neuromuscular disorders; many of which are genetic in aetiology, and often presenting in infancy or childhood. Until recently, apart from the inflammatory myopathies, it was a common misconception among general physicians that these disorders are rare and untreatable; and management is essentially supportive only. In this lecture, I shall highlight several muscle disorders which present not in the paediatric but in the adult Malaysian population and for which specific treatments are now available.